Optimized functional and structural design of dual-target LMRAP, a bifunctional fusion protein with a 25-amino-acid antitumor peptide and GnRH Fc fragment - Meng Li; Hanmei Xu; Junzhi Wang (Elsevier, 2020)
To develop fusion protein of a GnRH Fc fragment and the integrin targeting AP25 antitumor peptide for GnRH receptor-expressing cancer therapy. The LMRAP fusion protein was constructed. A transwell invasion assay was performed. The gene mRNA and protein levels of GnRHR-I, α5β1, and αvβ3 in different cancer cell lines were assessed. Cell proliferation was measured using a cell counting kit-8. An antagonist assay was performed on GnRH receptors. Anti-tumor activity was evaluated with a mouse xenograft tumor model. Immunohistochemistry (IHC) was applied to detect CD31 and CD34 expressions. Pharmacokinetic characteristics were determined with an indirect competition ELISA. The developed bifunctional fusion protein LMRAP not only inhibited HUVEC invasion, but also inhibited proliferation of GnRHR-I, α5β1, and αvβ3 high expression cancer cells. The IC50 for LMRAP in the GnRH receptor was 6.235 × 10−4 mol/L. LMRAP significantly inhibited human prostate cancer cell line 22RV1 proliferation in vivo and in vitro. LMRAP significantly inhibited CD31 and CD34 expressions. The elimination half-life of the fusion protein LMRAP was 33 h in rats. The fusion protein made of a GnRH Fc fragment and the integrin targeting AP25 peptide retained the bifunctional biological activity of GnRHR blocking, angiogenesis inhibition, prolonged half-life and good tolerance. KEY WORDS: Fusion protein, GnRH, Integrin, Angiogenesis, Prostate cancer